2021
DOI: 10.1111/ejn.15415
|View full text |Cite
|
Sign up to set email alerts
|

Brain microstructural changes in mice persist in adulthood and are modulated by the palmitoyl acyltransferase ZDHHC7

Abstract: For a long time, mice have been classified as adults with completely mature brains at 8 weeks of age, but recent research suggests that developmental brain changes occur for up to 6 months. In particular, adolescence coincides with dramatic changes of neuronal structure and function in the brain that influence the connectivity between areas like hippocampus and medial prefrontal cortex (mPFC). Neuronal development and plasticity are regulated in part by the palmitoyl acyltransferase ZDHHC7, which modulates str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(144 reference statements)
0
11
0
Order By: Relevance
“…Performing CFC in mice at 5 months of age allowed mice to recover from anesthesia and the stress of MRI imaging and enabled us to prepare for and arrange CFC assays. We are confident that our experimental design did not confound the correlations between dMRI values and CFM observed in Ntg mice ( Figure 9 ) because Ntg mice do not exhibit behavioral differences between 3 and 6 months of age (data not shown), and because mice are not expected to show differences in microstructure between 3 and 5 months of age ( Flurkey et al, 2007 ; Hammelrath et al, 2016 ; Kerkenberg et al, 2021 ). It is important to mention that no correlations between dMRI values and CFM performance were significant after FDR-adjustment.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Performing CFC in mice at 5 months of age allowed mice to recover from anesthesia and the stress of MRI imaging and enabled us to prepare for and arrange CFC assays. We are confident that our experimental design did not confound the correlations between dMRI values and CFM observed in Ntg mice ( Figure 9 ) because Ntg mice do not exhibit behavioral differences between 3 and 6 months of age (data not shown), and because mice are not expected to show differences in microstructure between 3 and 5 months of age ( Flurkey et al, 2007 ; Hammelrath et al, 2016 ; Kerkenberg et al, 2021 ). It is important to mention that no correlations between dMRI values and CFM performance were significant after FDR-adjustment.…”
Section: Discussionmentioning
confidence: 88%
“…At 5 months of age, after preliminary analysis had demonstrated effects of strain on brain microstructure and after mice had recovered from anesthesia, these mice underwent CFC. As mice between three and 6 months of age exhibit similar health and macro- and microstructural neural features ( Flurkey et al, 2007 ; Hammelrath et al, 2016 ; Kerkenberg et al, 2021 ), this experimental timeline enabled us to investigate (a) if brain microstructure varied with strain, sex, or 5XFAD genotype, (b) if short- and long-term fear memory varied with strain, sex, or 5XFAD genotype, and (c) if strain-related dMRI measurements could predict cognitive health in Ntg mice, thus determining the likelihood that brain microstructure confers brain reserve to AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies in search results have explored their function in cancer, compared to few studies in organ development. Nicole et al demonstrated that ZDHHC7 deficiency changes the brain microstructure and connectivity in young people between 11 and 17 weeks of age, suggesting that palmitoylation plays an important role during the early stages of brain development [ 39 ]. Similarly, studies have shown that due to the PPT1 expression pattern differing from the two other lysosomal enzymes implicated in NCL disease, PPT1 has a distinctive role in brain development [ 8 ].…”
Section: Resultsmentioning
confidence: 99%